ASPEK HUKUM PEMBANGUNAN PERUMAHAN PASCA PUTUSAN MAHKAMAH KONSTITUSI (MK) BAGI MASYARAKAT BERPENGHASILAN RENDAH (MBR) - Hudi Karno Sabowo (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2013)
In Indonesia, according to information from Deputi Bidang Pembiayaan Kementerian Perumahan Rakyat, there are millions of people who do not own their own home. The problem that frequently encountered is the problem of lack of funds. Distribution of the mortgages loan had not yet reached the low-income people. The potential distribution of mortgages loan for low-income people reached 34 million people. However, opportunities for low-income people to have decent housing was constrained by the government with the issuance of Undang-Undang Nomor 1 Tahun 2011 on Housing and Settlement Region set a minimum floor area of 36m2 house (square meters). With that restriction the price of the house would become increasingly unaffordable for the low-income people. Constraints are contained in Article 22 paragraph (3). The full written are thus "Spacious single-story home and home series has a size of at least 36 square meters."This terms cause The Real Estate Developer facing difficulties in land acquisition or construction of housing for the low-income people